Exploring Students' Creative Thinking Skills: A Design of Reliable Instrument in term of Assessing Creative Thinking on Temperature and Heat Concepts - Ahmad Maqruf; Andi Suhandi; Achmad Samsudin; Mustafa Sozbilir; Hasan Ozgur Kapici; Hadi Nasbey; Eki Nugraha (Journal of Natural Science and Integration, 2025)
This study aims to develop and validate an instrument for assessing creative thinking skills on the topic of temperature and heat among high school students. A quantitative research design was employed, with data analysis conducted using the Rasch model. The study involved 136 grade XI students from two high schools in West Bandung Regency, consisting of 51 male and 85 female participants. The Rasch analysis results indicated a Cronbach’s alpha of 0.78 (good) and an item reliability value of 0.97 (excellent). However, minor revisions are required in the wording of three items to improve linguistic clarity. The percentage distribution of creative thinking indicators was as follows: fluency (70.34%), flexibility (68.57%), originality (60.13%), and elaboration (61.76%). These findings reveal that students’ creative thinking is predominantly characterized by fluency, suggesting that they are relatively proficient at generating multiple ideas based on given problems, likely due to a good understanding of the material. Nevertheless, further instructional efforts are needed to foster higher levels of creative thinking, particularly in flexibility, originality, and elaborationKeywords: creative thinking skills test, temperature and heat concepts, rasch analysis